2021
DOI: 10.1002/adom.202100670
|View full text |Cite
|
Sign up to set email alerts
|

Diffracted Beams from Metasurfaces: High Chiral Detectivity by Photothermal Deflection Technique

Abstract: Measurements of difference in optical interactions between circularly polarized excitations of opposite handedness (circular dichroism) are highly important for both natural and artificial chiral structures. Here the photothermal deflection technique is proposed as a method to detect the optical chirality of a metasurface, analyzing the diffracted beams by the metasurface itself. Two metasurfaces are investigated, based on Au and Ag. The samples are fabricated by nanosphere lithography, with a tilted depositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…More importantly, the same sample can be used in the range around 780 nm to obtain opposite CD, by simply rotating the sample with respect to ϕ. Another interesting feature of such metamaterial could be its diffractive behavior in the high energy range, namely, the intensity of the orders diffracted to the glass in such samples strongly depend on the excitation handedness . Experimental realization of this design and its diffractive properties would allow us to reach shorter wavelengths (in the blue absorbing range of chiral molecules), and it is the subject of future work.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, the same sample can be used in the range around 780 nm to obtain opposite CD, by simply rotating the sample with respect to ϕ. Another interesting feature of such metamaterial could be its diffractive behavior in the high energy range, namely, the intensity of the orders diffracted to the glass in such samples strongly depend on the excitation handedness . Experimental realization of this design and its diffractive properties would allow us to reach shorter wavelengths (in the blue absorbing range of chiral molecules), and it is the subject of future work.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The fabrication cost of future chiral nanosensors can be lowered by using self-assembling approaches for extrinsic chirality. Nanosphere lithography or self-assembled nanowire growth can be combined with tilted plasmonic deposition to obtain high-quality samples, which exhibit extrinsic chirality. Moreover, we could even completely avoid the nanofabrication processes if we consider chirality in naturally hyperbolic media, such as van der Waals materials. One such example is a bilayer structure of twisted hexagonal boron nitride (hBN) slabs; even though hBN lacks in-plane anisotropy, the twist between the two layers leads to a difference in transmission of left and right circular polarizations (LCP and RCP, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously proposed the inplane and shape breaking of symmetry in elliptical nanohole arrays (ENHA), and showed that such simple geometries lead to interesting chiro-optical effects in the near-infrared range [2][3][4]. These samples can be fabricated by means of low-cost, nanosphere lithography [2,3,5,6] and further optimized to giant CD in absorption and transmission [4].…”
Section: Introductionmentioning
confidence: 99%
“…We previously proposed metasurfaces based on polystyrene nanospheres and covered by metal for various chiro-optical effects governed by extrinsic chirality. Namely, we measured different absorption [4], extinction [5] and diffraction [6] of impinging circular polarizations of opposite handedness. In these works, we excited the nanostructures with left or right circular polarizations (LCP and RCP, respectively), and monitored the total intensity of the transmitted or absorbed light.…”
Section: Introductionmentioning
confidence: 99%
“…In these works, we excited the nanostructures with left or right circular polarizations (LCP and RCP, respectively), and monitored the total intensity of the transmitted or absorbed light. We used conventional (transmission) methods [5], as well as highly sensitive photothermal effects [4,6]. Another interesting degree of freedom is the control of the polarization state in the output light, after the beam interacts with the metasurface.…”
Section: Introductionmentioning
confidence: 99%